2005
DOI: 10.1073/pnas.0500469102
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of type II NADH:menaquinone oxidoreductase represent a class of antitubercular drugs

Abstract: Mycobacterium tuberculosis (Mtb) is an obligate aerobe that is capable of long-term persistence under conditions of low oxygen tension. Analysis of the Mtb genome predicts the existence of a branched aerobic respiratory chain terminating in a cytochrome bd system and a cytochrome aa3 system. Both chains can be initiated with type II NADH:menaquinone oxidoreductase. We present a detailed biochemical characterization of the aerobic respiratory chains from Mtb and show that phenothiazine analogs specifically inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
292
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(309 citation statements)
references
References 30 publications
11
292
0
3
Order By: Relevance
“…Maintaining a Energy metabolism of nutrient-starved M. tuberculosis constant ATP level was demonstrated to be critical for the survival of hypoxic M. tuberculosis, and the respiratory enzyme Ndh-2, but not Ndh-1, was shown to be required for the maintenance of ATP homeostasis (Rao et al, 2008). Various groups have reported that tubercle bacilli are susceptible to phenothiazines, a class of known Ndh-2 inhibitors (Amaral et al, 1996;Teh et al, 2007;Weinstein et al, 2005;Yano et al, 2006). The Rubin lab demonstrated the bactericidal activity of phenothiazine compounds on nutrient-starved M. tuberculosis (Xie et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining a Energy metabolism of nutrient-starved M. tuberculosis constant ATP level was demonstrated to be critical for the survival of hypoxic M. tuberculosis, and the respiratory enzyme Ndh-2, but not Ndh-1, was shown to be required for the maintenance of ATP homeostasis (Rao et al, 2008). Various groups have reported that tubercle bacilli are susceptible to phenothiazines, a class of known Ndh-2 inhibitors (Amaral et al, 1996;Teh et al, 2007;Weinstein et al, 2005;Yano et al, 2006). The Rubin lab demonstrated the bactericidal activity of phenothiazine compounds on nutrient-starved M. tuberculosis (Xie et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…17 It is worth mentioning that this enzyme is not found in the mammalian mitochondria. The fundamental role of NDH-2 in Mtb respiration is supported by a wide range of biochemical 18 and transcriptional studies. 19 The Mtb genome contains two copies of ndh genes (ndh and ndhA).…”
Section: T He Contributory Driving Force Of Tuberculosis (Tb) Ismentioning
confidence: 99%
“…17,21 The effect of ndh deletion mutant lacking NDH-2 on bacterial growth under various culture conditions and on animal infection has been reported. 18 Phenothiazines (a class of antipsychotic drugs) are reported to be inhibitors of NDH-2. 17 This class of compounds is known to inhibit the growth of bacteria in vitro as well as bacteria inside macrophages.…”
Section: T He Contributory Driving Force Of Tuberculosis (Tb) Ismentioning
confidence: 99%
“…Historically, they were used to demonstrate the construction of respiratory chains from individual enzymes and Q 10 , but their capabilities have not (with very few exceptions31) been exploited for detailed mechanistic studies. Furthermore, many quinone antagonists are already used as pharmaceuticals or pesticides,32, 33 and bioenergetic enzymes specific to parasites and phytopathogenic fungi (including the alternative NADH dehydrogenase and AOX) are being investigated as drug targets 34. 35 Our self‐assembled Q 10 PL system enables candidate drugs and inhibitors to be competed against physiologically relevant quinone substrates to provide properly defined and robust inhibitor dissociation constants for translational research.…”
mentioning
confidence: 99%